Socio-spatial Patterns of Age Disparity Between Widow and Widower in North-East India - Das, Sriparna; Kar, Bimal K. (National Geographical Journal of India, 2022)
Widowhood continues to be a social stigma even in 21st century. In fact, the widows constitute 7.36% of female population in the country. However, there exists a considerable spatial variation in the proportion of widows in different parts of the country depending on variation in population composition and associated socio-cultural practices. The scenario of widowhood is no less different in North-East India inhabited by a population of a diverse ethno-religious composition. The phenomenon of considerably high incidence of widowhood in the region is largely the result of the prevalence of higher life expectancy among females, age differential between husband and wife, restrictions in widow remarriage and polygamy. With this background an attempt has been made in this paper to investigate the patterns of widowhood in different parts of North-East India as compared to India as a whole during 2001-2011 with respect to age, inter-religion, rural-urban and caste-tribe variations. The study is primarily based on secondary data obtained from various Census of India publications and partly based on primary data collected from selected localities in and around Guwahati city. The data so obtained have been analysed and presented using meaningful statistical and cartographic techniques